Peaceful Places: An immersive, partecipatory performance - Landi, Margherita (Mimesis Journal, 2024)
Peaceful Places, Margherita Landi and Agnese Lanza reimagine the hug through VR, emphasizing human connection post-pandemic. Bodies are depicted as "peaceful places", creating a safe space for experiencing proximity and fostering intimacy and empathy. Users engage in a VR experience mimicking hugs, promoting introspection and shared presence.